Biomechanical modelling for computation of knee joint torque in different strategies of stop-jump landing - Mahdieh, L.; Lenjannejadian, S.; Ghasemi, G.; Poorsina, M.; Mirtavoosi, S. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Knee injuries especially non-contact anterior cruciate ligament injury, is very common in sport activities and often occurs in landing. The purpose of this study was to recognize the risk factors and to recommend better landing strategies using dynamic modeling. For this purpose, the stop-jump landing was modeled using anthropometric, kinematic and kinetic data. The knee torque was calculated for different landing strategies. The result showed that the maximum knee torque for women was 42% more than men. When the knee flexion at the initial foot contact increased, the peak knee torque decreased. Finally, increasing the knee and hip angular displacement, the maximum knee torque decreased at first and then increased again. Therefore the knee flexion angle at initial foot contact and the knee and hip angular displacement are effective factors in reducing knee injuries.